Destination Branding Indonesia Sebagai Destinasi Wisata Halal - Subarkah, Awafi Ridho; Junita Budi Rachman; Akim (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2020)
This study aims to discuss the destination branding of Indonesia using halal tourism instruments to increase tourist arrivals, especially from the Middle East market, and make Indonesia the world's halal tourist destination. This research uses descriptive qualitative method with the concept of destination branding and public diplomacy. The results of this study indicate that Indonesia embarked on destination branding by establishing the Halal Tourism Indonesia Logo, Halal Tourism Indonesia: The Halal Wonders, to describe its halal tourist destinations, then designating three regions that are considered ready to be the leading halal tourist destinations, namely Lombok (Friendly Lombok), Aceh (The Light of Aceh), and West Sumatra (Taste of Padang) as seen from facilities and services that meet the criteria halal tourism and won the world's best halal tourism award representing Indonesia at the World Halal Travel Summit in Abu Dhabi 2015 and 2016. In addition, Indonesia also made efforts to halal tourism diplomacy through familiarization trips, attending national and international exhibitions, and through the media and seen the results of the increasing number of Middle Eastern tourists visiting as the primary target market for halal tourism.